2022
DOI: 10.1123/jmld.2020-0069
|View full text |Cite
|
Sign up to set email alerts
|

The Test of Gross Motor Development—Third Edition: A Bifactor Model, Dimensionality, and Measurement Invariance

Abstract: Aim: To examine the latent structure of the Test of Gross Motor Development—Third Edition (TGMD-3) with a bifactor modeling approach. In addition, the study examines the dimensionality and model-based reliability of general and specific contributions of the test’s subscales and measurement invariance of the TGMD-3. Methods: A convenience sample of (N = 496; Mage = 7.23 ± 2.03 years; 53.8% female) typically developed children participated in this study. Three alternative measurement models were tested: (a) a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
3
0
2
Order By: Relevance
“…We found that the KTK can be considered an appropriate instrument to simultaneously evaluate and compare MC across sex and age groups. Our findings are similar to Garn and Webster (2018) and Salami et al (2021) who found measurement invariance for sex using the TGMD-2 and the TGMD-3, respectively, providing (partial) agreement with the current study findings. In contrast to this study, a Brazilian study (Moreira et al, 2019) found noninvariance for the factor loadings, item intercepts, and residual variances across sex and age groups, so a stable relationship between the KTK structure and test score was not determined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the KTK can be considered an appropriate instrument to simultaneously evaluate and compare MC across sex and age groups. Our findings are similar to Garn and Webster (2018) and Salami et al (2021) who found measurement invariance for sex using the TGMD-2 and the TGMD-3, respectively, providing (partial) agreement with the current study findings. In contrast to this study, a Brazilian study (Moreira et al, 2019) found noninvariance for the factor loadings, item intercepts, and residual variances across sex and age groups, so a stable relationship between the KTK structure and test score was not determined.…”
Section: Discussionsupporting
confidence: 91%
“…One study on the TGMD-2 (Garn & Webster, 2018) showed measurement invariance for sex but not for age. Similarly, another study of the TGMD-3 (Salami et al, 2021) also found measurement invariance for sex. We hypothesized the KTK will be measurement invariant for sex and age groups.…”
mentioning
confidence: 73%
“…All collaborators who participated in the project had experience in motor development research and significant experience in using, analyzing, and interpreting motor skill assessments like the TGMD. Evidence of TGMD assessment reliability was previously presented in the primary original studies from six countries (Spain, Italy, Brazil, Australia, Iran, and USA) 25–34 …”
Section: Methodsmentioning
confidence: 97%
“…Tenho mantido uma parceria com professores da Educação Física da UFMG e de universidades do exterior. Nessa parceria tenho realizado uma extensão técnica em psicometria, principalmente relacionada à investigação da validade de instrumentos de medida (Costa, 2012;Reis, 2021;Salami, 2021).…”
Section: Parcerias Acadêmicas E Seus Produtosunclassified